Analisis in-Silico pGEM-GLL Recombinan Glukoamilase Saccharomycopsis fibuligera R64 - Pasjan Satrimafitrah (Biocelebes, 2010)
Saccharomycopsis fibuligera is yeast with high amylolitic activity. The local strain, S. fibuligera R64 has been reported to produce starch hydrolyzing enzymes, -amylase dan glucoamylase. Glucoamylase is one of the extracellular enzymes that enable to breakdown starch in starch processing, thus has potential to be developed and applied in starch processing industry, such as glucose syrup production. Wild type microorganism-producing glucoamylase normaly express low level of enzyme, while high level production and low cost enzymes are needed in many industries. To obtain strains with superior properties, a recombinant DNA is used and Pichia pastoris is a suitable expression host for producing glucoamylase at high level. Gene encoding glucoamylase S. fibuligera R64 (GLL) has been amplified and cloned into pGEM-T vector. A set of primers (Glu-F and Glu-R) was designed based on the published nucleotide sequence (Acc. No M17355). Restriction analysis of pGEM-GLL by using EcoRI and XhoI showed a ~4.500 kb DNA fragment which confirmed the size of pGEM-T vector containing GLL. This research aimed to analyze pGEM-GLL S. fibuligera R64 in silico. Gene alignment of GLL S. fibuligera R64 with GLU1 S. fibuligera showed 99 % homology. Based on in silico translation analysis, there were several nucleotide difference compared to the published sequence which result in amino acid differences, namely E27D, N46D, dan A376V. Hence it is possible that S. fibuligera R64 has different properties from other known S. fibuligera. Key words: Glucoamylase, S. fibuligera, E. coli TOP10F’, PCR, in silico analysis.